Herbicide resistance in Leptochloa chinensis (L.) Nees populations from different regions of Jiangsu Province, China: sensitivity differences and underlying mechanisms - Peng Xu; Ke Wang; Yawen Ju; Yousheng Fu; Axiu Zhu; Kaige Cao; Hongchun Wang (Frontiers in Plant Science)
Leptochloa chinensis (L.) Nees, a noxious weed species commonly found in rice fields, has become a significant challenge in Jiangsu Province, China, as it has developed resistance to multiple herbicides due to extensive and continuous herbicide use in recent years. Therefore, this study was conducted to elucidate sensitivity differences and the mechanisms underlying the resistance of L. chinensis (L.) Nees populations to commonly used herbicides across different regions of Jiangsu Province, China. A whole-plant bioassay was used to assess the sensitivity of 46 L. chinensis populations collected from various areas within Jiangsu to several herbicides frequently applied in paddy fields, including: cyhalofop-butyl, fenoxaprop-P-ethyl, pyraclonil, benzobicyclon, anilofos, and oxaziclomefone. After treatment with cyhalofop-butyl, 38 out of 46 populations showed relative resistance-index values that were over four times that of the controls, indicating significant resistance to cyhalofop-butyl. All 41 cyhalofop-butyl-resistant populations showed cross-resistance to fenoxaprop-P-ethyl but remained susceptible to pyraclonil, benzobicyclon, anilofos, and oxaziclomefone. The proportion of populations resistant to acetyl-CoA carboxylase (ACCase)-inhibiting herbicides increased progressively from the south to the north of Jiangsu. Cross-resistance was evident between cyhalofop-butyl and fenoxaprop-P-ethyl; however, all resistant populations were susceptible to pyraclonil, benzobicyclon, anilofos, and oxaziclomefone. Furthermore, mutations in the ACCase gene were identified as a crucial mechanism for cyhalofop-butyl resistance. Specifically, we found ACCase mutations I1781L, W1999C, W2027C/L/S, I2041N, and D2078G in cyhalofop-butyl-resistant L. chinensis populations, among which, W1999C and W2027C accounted for a relatively high proportion, while I1781L, W2027L/S, I2041N, and D2078G were found in one population each. ACCase gene mutations are seemingly a key mechanism for the development of resistance to cyhalofop-butyl, thus, our study provides useful information for developing effective weed-management strategies for controlling this noxious weed species, while ensuring sustainable agricultural practices.